(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In vocational education, it is advisable to integrate the ideas of sustainable development into curricula and programs to achieve Sustainable Development Goals. The study was conducted in order to identify opportunities for future primary school teachers to develop sustainable development skills in secondary vocational education when teaching mathematical disciplines. The ways of integrating the ideas of sustainable development, the formation of sustainable development competencies into the practice of training future primary school teachers of secondary vocational education are identified and specified by examples. The results of the study contribute to the integration of the ideas of sustainable development into the educational process, namely into the main professional educational programs, work programs, lesson development, assessment tools for the formation of sustainable development competencies in primary school teachers.